POVERTY, CHILD LABOUR AND ACCESS TO SCHOOLING IN OYO STATE - Adeagbo, Joseph Olusegun; Mosobalaje, Risikat Olaitan (African Journal of Educational Management, 2023)
This empirical study investigated the intricate interplay among poverty, child labour, and access to schooling in Oyo State, Nigeria. The study employed self-designed questionnaire to collect the useful information from the respondents. Collected data were analysed using simple frequency counts and Non-Parametric Chi Square statistic. Findings from the results showed that parental neglect and displacement due to natural factors and lack of proper nutrition caused child labour. It was also revealed that child abuse and social vices as source of poverty has positive relationship with child labour. It was finally revealed that poverty has negative effect on schooling. It was recommended that government should create programmes that will improve access to schooling and policy intervention aimed at breaking the cycle of poverty and fostering access to quality education for all children in Oyo State.